Combined effects of arbuscular mycorrhizal fungi and exogenous cytokinins on pomegranate (Punica granatum) under two contrasting water availability conditions - Bompadre, Maria Josefina (2015)
To our knowledge, there are no studies on the interactive effects of inoculation with arbuscular mycorrhizal fungi and cytokinin addition to plants under drought stress. We investigated the potential protective effect of arbuscular mycorrhizae on pomegranate plants, combined with exogenous cytokinin addition, under two contrasting soil water availability regimes. Our results showed that exogenous cytokinin addition enhances plant biomass, shoot to root ratio and water content, as well as increasing the anthocyanin content. However, a combination of AM fungal inoculation and cytokinin addition did not result in a synergistic protective effect against water stress. Plants were equally well protected against this stress by cytokinin spraying alone. The improvement of pomegranate growth was due mainly to exogenous cytokinin addition. Photosynthesis was promoted both by mycorrhizal inoculation alone and by exogenous cytokinin addition. The main protection against oxidative stress caused by drought was via enhanced accumulation of anthocyanins when the plants were sprayed with cytokinins. When cytokinins were used, the photosynthesis apparatus was also protected.